The daytime indoor and outdoor temperatures of the subterranean termite Coptotermes curvignathus Holmgren (Isoptera: Rhinotermitidae) tunnel. Issue 2 (July 2021) - Arinana; Philippines, I; Koesmaryono, Y; Sulaeha, S; Maharani, Y; Indarwatmi, M
Abstract: The termite's life cycle is affected by weather conditions, including temperature. To keep its activities safe from any direct light, termites design tunnels to hide. This research aims to analyze the temperature subterranean termite tunnel Coptotermes curvignathus inside and outside the room. Tunnel temperature measurement was carried out by thermocouple tool. The research was conducted at Forest Products Research and Development Center, Gunung Batu, Bogor. The results showed that the temperature in the tunnel's indoor ranged between 25.8 - 34.1 °C while temperatures in the tunnel's outdoor ranged between 25.0 - 32.7 °C. The tunnel's indoor temperature was 0.8 °C to 1.4 °C warmer than the tunnel's outdoor temperature, while the surrounding's indoor temperature was 0.2 °C warmer than the surrounding's outdoor temperature.